Degradation kinetics and thermodynamic analysis of betalains on microencapsulated beetroot juice using maltodextrin and sweet potato starch (Scientia Agropecuaria, 2021)
Natural colorants have become important due to the health-benefits for humans. In that sense, it is important to evaluate the degradation kinetics of these components, in order to establish the stability under different processing and/or storage conditions. This study provides experimental and simulated results about the degradation of betalains in microencapsulated beetroot juice. Maltodextrin solution (MDX 10%) and sweet potato starch solution (SPS 2%) in proportions of 40MDX:60SPS, 20MDX:80SPS and 0MDX:100SPS were used as microencapsulating agents. The thermal degradation of betalains in the microencapsulated powders was evaluated at three temperatures (6, 19 and 30 °C) in order to predict the behavior under different conditions, using the first-order kinetic model. The kinetic parameters were identified using linear regression on the logarithmic curves of the experimental data to obtain the Arrhenius equations. The highest content of betalains was 2.58 mg/g and the lowest activation energy value was 48.71 KJ/mol, with both values corresponding to the powder that was microencapsulated with 20MDX:80SPS. The above results suggest high betalain stability in this powder, since there was less sensitivity to temperature in comparison to the rest of the powders. Additionally, some thermodynamic parameters were evaluated, which confirmed that the process is non-spontaneous and irreversible. The results obtained from this study, could be a useful tool to predict the minimal losses during processing, and gives the possibility to improve and select the food products where this kind of natural colorant can be applied.